THE AFGHANISTAN FACTOR: ITS INFLUENCE ON REGIONAL COMPETITION IN SOUTH ASIA - Saqib Ullah Khan; Jafar Nazir; Zahida Jabeen (Journal of Religion and Society, 2025)
The role of Afghanistan in shaping regional dynamics in South Asia is profound and multifaceted, influencing security, political alignments, and economic developments across the region. This article examines Afghanistan's pivotal position at the crossroads of South Asia and Central Asia, and how its geopolitical significance impacts regional competition, particularly in the context of the withdrawal of international forces and the resurgence of the Taliban. The analysis begins with an overview of Afghanistan's historical role as a buffer state and its strategic importance in the "Great Game" of the 19th and 20th centuries. The focus then shifts to contemporary issues, detailing how Afghanistan's security landscape affects neighboring countries like Pakistan, India, and Iran. The study highlights the complex interplay of insurgent groups, state actors, and external powers within Afghanistan, which perpetuates instability and fosters regional power struggles. Key aspects discussed include the implications of Afghanistan's instability on cross-border terrorism, narcotics trafficking, and refugee flows, which pose significant challenges to regional security and cooperation. The paper also explores the strategic interests of major powers in the region, such as the United States, Russia, and China, and their influence on Afghanistan’s internal politics. Moreover, the article examines the economic implications of peace in Afghanistan, particularly the potential for regional connectivity and trade routes that could link South and Central Asia. The conclusion underscores the need for a coordinated regional approach to address the multifarious challenges posed by Afghanistan, suggesting pathways towards collaborative security frameworks and economic integration. In essence, "The Afghanistan Factor: Its Influence on Regional Competition in South Asia" provides a detailed analysis of how Afghanistan's geopolitical challenges are central to understanding and addressing regional competition and cooperation in South Asia. Keywords: Afghanistan, regional competition, South Asia, Central Asia, geopolitical significance, security landscape, regional power struggles, external powers, cross-border terrorism, economic connectivity.